Modified electrode for electrochemical analysis. - Yusof, Nor Azah; Daud, Nurulhaidah (2009)

(untitled)
The electrochemical sensor for As(III) were developed by using carbon nanotube/amino acid modified platinum electrode using cyclic voltammetry. Experimental conditions such as pH, supporting electrolyte and scan rate were optimized. It was observed that the modified electrode has significantly superior analytical performance in determination as As(III) compared to the unmodified electrode. The determination of As(III) by using modified electrode was reproducible with R.S.D of 7.33%. Determination of As(III) was observed to be free interference at pH 4 acetate buffer. The electrocatalytic redox peak current of As(III) showed a linear response towards different concentration of As(III) and linear calibration cuves were obtained. The sensitivity expressed as the slope of the linear regon of the calibration curve. This method was also examined for determination of As(III) in some real samples, such as industrial waste water from wood industry and electroplating industry.